Efficacy and Safety of Ensitrelvir in Patients With Mild-to-Moderate Coronavirus Disease 2019: The Phase 2b Part of a Randomized, Placebo-Controlled, Phase 2/3 Study. (7th December 2022) - Mukae, Hiroshi; Yotsuyanagi, Hiroshi; Ohmagari, Norio; Doi, Yohei; Sakaguchi, Hiroki; Sonoyama, Takuhiro; Ichihashi, Genki; Sanaki, Takao; Baba, Keiko; Tsuge, Yuko; Uehara, Takeki
Abstract: Background: This phase 2b part of a randomized phase 2/3 study assessed the efficacy and safety of ensitrelvir for mild-to-moderate coronavirus disease 2019 (COVID-19) during the Omicron epidemic. Methods: Patients were randomized (1:1:1) to orally receive ensitrelvir fumaric acid 125 mg (375 mg on day 1) or 250 mg (750 mg on day 1) or placebo once daily for 5 days. The co-primary endpoints were the change from baseline in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) titer on day 4 and time-weighted average change from baseline up to 120 hours in the total score of predefined 12 COVID-19 symptoms. Safety was assessed through adverse events. Results: A total of 341 patients (ensitrelvir 125-mg group: 114; ensitrelvir 250-mg group: 116; and placebo group: 111; male: 53.5–64.9%; mean age: 35.3–37.3 years) were included in the efficacy analyses. The change from baseline in SARS-CoV-2 titer on day 4 was significantly greater with both ensitrelvir doses than with placebo (differences from placebo: −0.41 log10 50% tissue-culture infectious dose/mL; P < .0001 for both). The total score of the 12 COVID-19 symptoms did not show a significant difference between the ensitrelvir groups and placebo group. The time-weighted average change from baseline up to 120 hours was significantly greater with ensitrelvir versus placebo in several subtotal scores, including acute symptoms and respiratory symptoms. Most adverse events were mild in severity. Conclusions: Ensitrelvir treatment demonstrated a favorable antiviral efficacy and potential clinical benefit with an acceptable safety profile. Clinical Trials Registration: Japan Registry of Clinical Trials: jRCT2031210350 (https://jrct.niph.go.jp/en-latest-detail/jRCT2031210350 ) Abstract : Treatment with 5-day, once-daily, oral ensitrelvir demonstrated a reduction in viral titer and viral RNA against the SARS-CoV-2 Omicron variant, potential clinical benefit, and an acceptable safety profile in patients with mild-to-moderate COVID-19 in a phase 2b study setting.